Warm water immersion to reduce hypertension among elderly - Prasetya, Erizal Yoga; Wahyuningtyas, Eka Sakti; Subrata, Sumarno Adi (Universitas Muhammadiyah Magelang, 2023)
Hypertension is a cardiovascular disease characterized by elevated blood pressure. However, studies on the use of water immersion to reduce hypertension are scarce in the literature. Therefore, this study aims to provide an overview of the application of warm water foot soaks with a mixture of salt to reduce blood pressure in elderly individuals with hypertension. The research design for this study utilizes a case study approach with purposive sampling. The author systematically observed hypertension patients and collected factual data. A sample of elderly patients with stage 1 hypertension, aged 56 years, was selected. Data was collected through observation, interviews, and documentation. This study indicates that warm water foot soak therapy with a mixture of salt can reduce both systolic and diastolic blood pressure after 6 sessions, with each session lasting 15–20 minutes. The application of warm water foot soaks with a mixture of salt can lower blood pressure due to the dilation of blood vessels, which reduces muscle tension and increases tissue metabolism. Warm water foot soaks with a mixture of salt appear to be an effective method for reducing blood pressure in elderly patients with hypertension. Further research is recommended to explore this therapy's long-term benefits and potential applications. Keywords: Health innovation; healthcare professionals; complementary therapy for hypertension; warm water soak; chronic illness.